Speak what we feel (not what we ought to say) : reflections on literature and faith - Buechner, Frederick, 1926- ([San Francisco] : HarperSanFrancisco, 2001)
Frederick Buechner explores how four authors who have influenced his own life have dealt with mortality, failure, and tragedy.
Adult
Adult
Library Journal
Keywords: English literature -- History and criticism; Christianity and literature -- Great Britain -- History; Chesterton, G. K. -- 1874-1936.; Hopkins, Gerard Manley, -- 1844-1889 -- Criticism and interpretation; Twain, Mark, -- 1835-1910.; Shakespeare, William, -- 1564-1616.; Christianity and literature -- United States; Faith in literature; English literature -- History and criticism; Christianity and literature -- History; Chesterton, G. K. -- 1874-1936.; Hopkins, Gerard Manley, -- 1844-1889 -- Criticism; Twain, Mark, -- 1835-1910.; Shakespeare, William, -- 1564-1616.; Faith in literature